Ultranationalism and Ultra-Orthodoxy: The Case of Shas - Leon, Nissim (Politikologija religije, 2024)
Israeli scholarship has noted the prominence of hawkish and ultranationalist views among the Shas electorate, as well as the structural and historical conditions responsible for them. Attention has not, however, been paid to the contexts and the ways in which Mizrahi-Haredi discourse processes these views in its encounter with this population. The present article looks at one of the main components of the relationship between Shas and its supporters in Israel's social periphery - the teshuva movement. Fieldwork on the discourse of local teshuva preachers shows that they have used the ultranationalist message to illustrate the importance of adhering to Jewish religious tradition and relying on its rabbinical authorities. A complex and fluid version of religious ultranationalism was detected as well, one that demands communal separation but is not, however, averse to cultural interaction between Jews and Arabs.